REGIONAL AUTONOMY PROLIFERATION OF REGION AND PSEUDO LOCAL GOVERNMENT IN INDONESIA - M. Ali Imron (Jurnal Kawistara, 2011)
This paper discusses the other side of the potential negative effects, even failure, of the implementation of the decentralization policy in Indonesia. One cause of the demands to establish a new area is rent seeking, where local elites and local politicians try to regain power through the formation of new regions. One thing overlooked by scholars is the existence of local businessmen who also participated in the formation of new regions. Their presence did not appear as real as the local elites and party elites because they take roles behind the scenes as lenders; the group was later referred to as the “black market.” The existence of this black market in the regional areas is always necessary for an area’s local elites and political elites to regain power as one force.